Interactional Sociolinguistics: The Theoretical Framework and Methodological Approach to ELF Interaction Research - Toomaneejinda, Anuchit; Saengboon, Saksit (LEARN Journal: Language Education and Acquisition Research Network, 2022)
The prevalent use of ELF in global communication necessitates a rethinking of what theoretical frameworks and methodological approaches are appropriate to explain the changing and complex nature of intercultural interactions, particularly, those whereby English is recognised as a passport. This review accounts for ELF interactions in terms of Interactional Sociolinguistics (IS). In doing so, it discusses the characteristics and functions of IS taking into consideration the complexity of ELF contexts, most notably intercultural encounters that are prone to misunderstandings and communication breakdowns. Further, based on an analysis of previous studies on ELF, the paper characterises ELF interaction and its key components, and ELF interactional ecology using Interactional Sociolinguistics as a theoretical framework.